Farmacocinética pré-clínica e avaliação toxicológica preliminar da nova tiazolidinadiona desenvolvida para o tratamento do diabetes mellitus tipo 2: 5-(4-cloro-benzilideno)-3-(4-metil-benzil)-tiazolidina-2,4-diona (GQ-2) - Vieira, Carla Monalizi [UNESP] (2013)
The compound 5-(4-chloro-benzylidene)-3-(4-methyl-benzyl)-thiazolidine-2,4- dione (GQ-2), new thiazolidinedione drug, presents hypoglycemic activity by lowering the basal levels of insulin, glucose and leptin, associated with the increased insulin sensitivity. In addition, reduces body weight gain due to minor liquid retention. These results ratify GQ-2 as possible therapeutic alternative for the treatment of type 2 diabetes. In this work we investigated the pharmacokinetic profile and primary hepatic and renal toxicity of the compound GQ-2. This compound was administered in a single dose orally (12 mg/Kg) and intraperitoneally (12 mg/Kg) and intravenously (3 mg/Kg) in Wistar rats (n=25). After administration serial blood collections were taken through the femoral artery. The samples were processed and analyzed by a validated bioanalytical method, using UPLC system. The system consisted of an Acquity UPLC® equipped with a UV-visible detector operating at 330 nm. The separation was performed with BEH column (2.1 x 50 mm, 1,7 μm) as the eluting mobile phase consisted of a acetonitrile:water (80:20) in isocratic mode and flow of 0,4 mL/min. The mean pharmacokinetic parameters were calculated by the curves of plasma concentration versus time and expressed through the mean, median and IC (95). The administration of the GQ-2 single dose (3 mg/Kg) intravenously enables the construction of the plasma concentration versus time curve. The pharmacokinetic parameters were obtained: Cmax (ng/mL) 786,2 (534,62-1037,76), tmáx (h) 0,08, AUC0-t (ng/mL/h) 390, 84 (282,28-499,41), AUC0-inf (ng/mL/h) 411,60 (296,41-526,79), Cl (L/h/Kg) 8,0 (5,45-10,55), Vd (L/Kg) 45,6 (23,9-67,3), r areas (%) 0,95 (0,94-0,95), k or (min-1) 5,51 (4,7- 6,3), t½ (min) 0,13 (0,11-0,14), k or (min-1) 0,24 (0,08-0,39), t½ (min) 4,44 (2,14-6,74). For the administration of GQ-2 in a single dose orally (12 mg/Kg) and intraperitoneally (12 mg/Kg) was not possible to construct ...